Faktor-Faktor Yang Berhubungan Dengan Tindakan Mengemudi Tidak Aman Pada Supir Bus Sampri Trayek Medan – Dolok Sanggul - Irmayani Irmayani; Enaldihend Lumban Tobing (Jurnal Penelitian Kesmasy, 2018)
One of cause accidents is human error, which reflected in the dangerous behavior of driving a bus. Errors and violations can cause an accident to the driver itself and will harm the people around him. Based on everyday phenomena, it can be seen that many motorists violate traffic signs. This behavior of breaking traffic signs is one example of aggressive driving behavior that can endanger other road users. This study aims to explain the factors associated with unsafe driving action on Bus Sampri Driver in Medan Route - Dolok Sanggul. This research is an observational analytic survey using cross sectional design. The research was conducted at PT. Samosir Pribumi Transport Medan in October 2017-April 2018. The population in this study were all Bus Sampri drivers, Medan Dolok Sanggul Route and all passengers with the Medan-Dolok Sanggul destination. The sample in this study were 64 people where 32 people came from bus drivers and 32 people came from passengers who were taken using quota sampling technique. The research instrument uses a questionnaire. Data were analyzed using chi-square test with a confidence level of 95% (alpha = 5%). The results showed that there was a relationship between duration of work (p = 0.024), work period (p = 0.024), rest period (p = 0.024), work schedule (p = 0.035) with unsafe driving action. Drivers are advised to maintain health so that they do not experience physical or psychological health problems, be careful in driving and obey traffic signs so as not to endanger passengers.